IMPLEMENTASI PEMBERIAN BANTUAN HUKUM TERHADAP PEREMPUAN YANG MENGALAMI PERMASALAHAN KEKERASAN SEKSUAL DI KOTA PEKANBARU - Saragih, John Meidi; Rahmadan, Davit; Elmayanti, Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
Sexual violence is a crime that is currently receiving a lot of publicattention. The media often covers news about sexual violence crimes. As a type ofclassic crime, this crime has existed for a long time and will continue to exist anddevelop along with human culture. The aim of this research is to find out how thePekanbaru legal aid system helps victims of sexual violence. Sociological legalresearch is the research approach used in this research. A literature review andinterviews in the field of law constitute this research. The implementation of legalaid for women who experience sexual violence in Pekanbaru is the focus of thisresearch debate. Primary, secondary and tertiary legal sources are used as datasources. As legal aid institutions, PBH Pekanbaru, UPT PPA Pekanbaru City,LBH Putra Bangsa Justice Forum and PBH Adin Siak.A woman who is a victim of sexual violence faces too many obstacles whenit comes to accessing justice or needing legal protection. Weak laws and negativeviews of victims of violence are considered to be the basic reasons why not manywomen report the violence they experience. And it becomes more difficult inlayers when the perpetrator is a public official or public figure. There is animbalance in power relations where the perpetrator may use his relations andpower to influence the victim's access to justice. This results in impunity forperpetrators while victims of violence do not have their rights to justice, truth andrecovery fulfilledLegal aid institutions As part of its initiative to protect women andchildren from sexual violence, the Indonesian government has offered legal aidthrough the Women and Children Protection UPT. People in Indonesia have feltthe benefits of community and government efforts in providing legal assistance.Based on a study by the Pekanbaru Legal Aid Center, PBH Pekanbaru as a lawfirm should naturally take legal action to help all its customers. The first line ofdefense against sexual violence is Psychosocial, Paralegal Post, Advocacy andSafe House.Keywords: Implementation, Provision Of Legal Aid, Women, Sexual Violence.